1981
DOI: 10.1246/cl.1981.1679
|View full text |Cite
|
Sign up to set email alerts
|

Trifluoromethylation of Carbonyl Compounds With Trifluoromethylzinc Iodide Under Ultrasonic Irradiation

Abstract: The trifluoromethylation of carbonyl compounds with trifluoromethylzinc iodide, prepared from trifluoromethyl iodide with ultrasonically dispersed zinc, smoothly proceeded to give corresponding α-trifluoromethyl carbinols in good yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(5 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…We found that cyclopropanation occurs readily with ordinary zinc and the preparation of zinc-copper couples could be avoided (15). Recently other workers reported similar observations using mossy zinc (20), and Kitazume and Ishikawa have shown that the reactions of zinc with perflouroalkyl iodides are also accelerated by ultrasonic waves (21).…”
Section: /C~c\supporting
confidence: 55%
“…We found that cyclopropanation occurs readily with ordinary zinc and the preparation of zinc-copper couples could be avoided (15). Recently other workers reported similar observations using mossy zinc (20), and Kitazume and Ishikawa have shown that the reactions of zinc with perflouroalkyl iodides are also accelerated by ultrasonic waves (21).…”
Section: /C~c\supporting
confidence: 55%
“…Synthesis of 1 ,butan-2-ol. This trifluoromethyl alcohol was synthesized from [1-13C]hydrocinnamaldehyde according to the procedure of Kitazume and Ishikawa (1981). The labeled hydrocinnamaldehyde was prepared as follows: (2-phenylethyl)magnesium bromide was prepared from (2-bromoethyl)benzene and magnesium turnings in dry ether.…”
Section: Methodsmentioning
confidence: 99%
“…Secondary carbinols, obtained by the addition of vinyl organometallics to trifluoroacetaldehyde [59] or perfluoroalkyl organometallics to unsaturated aldehydes (Scheme 22) [60][61][62] can be oxidized by Dess-Martin [63,64] or Swern [65] reagents or using MnO 2 [66] in dichloromethane to the α,β-ethylenic trifluoromethyl ketones in good yields. [66,67] It should be noted that the reduction of acetylenic CF 3 ketones using LiAlH 4 or NaBH 4 does not give CF 3 enones but the corresponding allyl alcohols [50,64,68].…”
Section: Scheme 21mentioning
confidence: 99%